1997
DOI: 10.1021/ic9700866
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Rhenium(I) and Rhenium(II) Amine Dinitrogen Complexes and the Characterization of an Elongated Dihydrogen Species

Abstract: A series of rhenium(I) dinitrogen complexes were prepared containing predominantly amine ligands. On the basis of infrared and electrochemical data, a system was selected that was anticipated to be a suitable precursor for an elongated dihydrogen complex. Upon oxidation by AgOTf, the dinitrogen ligand of fac-[Re(PPh(3))(PF(3))(dien)(N(2))](+) (3) is replaced with triflate to generate 13, fac-[Re(PPh(3))(PF(3))(dien)(OTf)]OTf, a convenient precursor to rhenium(II) and rhenium(I) amine complexes. Reduction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 27 publications
1
39
1
Order By: Relevance
“…[46] We found that the [Re III Br(tacn) (CO) 3 ] 2+ complex (7) is the likely first redox reactions either from the corresponding Re(i) or Re(iii) complexes. This is especially true for coordination compounds [41][42][43][44][45] 2 ] complexes (Scheme 1). [40] These simple ligand substitution reactions are a rare feature for a mononuclear 17-electron rhenium complex.…”
Section: The Cis-[rementioning
confidence: 99%
See 2 more Smart Citations
“…[46] We found that the [Re III Br(tacn) (CO) 3 ] 2+ complex (7) is the likely first redox reactions either from the corresponding Re(i) or Re(iii) complexes. This is especially true for coordination compounds [41][42][43][44][45] 2 ] complexes (Scheme 1). [40] These simple ligand substitution reactions are a rare feature for a mononuclear 17-electron rhenium complex.…”
Section: The Cis-[rementioning
confidence: 99%
“…[4] Thus, fewer than 50 articles comprise the entire literature of Re(ii) chemistry and these can be further reduced to 15 fundamental reports. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The rhenium chemistry of this oxidation state is dominated by phosphorus ligands. A few notable exceptions are complexes of binding ligands such aromatic amines or isocyanides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,16] As yet there are no reports in the literature of dicationic dihydrogen complexes of transition metals with the PF 3 ligand. Therefore, in continuation of our investigations on the heterolytic activation of molecular hydrogen we report here the first examples of dicationic dihydrogen complexes of iron and ruthenium with a trans-PF 3 ligand trans-[M(η 2 -H 2 )(PF 3 )(diphosphane) 2 ] 2ϩ (M ϭ Fe, diphosphane ϭ dppe; M ϭ Ru, diphosphane ϭ dppm, dppe).…”
Section: )(Pph 3 )(Pf 3 )(Dien)]mentioning
confidence: 99%
“…[48][49][50] Like the previously discussed polypyridal ligand set the new rhenium species also afforded a variety of dihapto-complexes (Scheme 3), with similar electronic properties. However, despite the success in once again reproducing the electronic requirements of the osmium system, η 2 -aromatic complexes remained elusive.…”
Section: +mentioning
confidence: 62%